Modulation of Stat-1 in Human Macrophages Infected with Different Species of Intracellular Pathogenic Bacteria - Giuditta Fiorella Schiavano; Sabrina Dominici; Laura Rinaldi; Alfonsina Mariarosaria Cangiano; Giorgio Brandi; Mauro Magnani (Journal of Immunology Research)
The infection of human macrophages by pathogenic bacteria induces different signaling pathways depending on the type of cellular receptors involved in the microorganism entry and on their mechanism(s) of survival and replication in the host cell. It was reported that Stat proteins play an important role in this process. In the present study, we investigate the changes in Stat-1 activation (phosphorylation in p-tyr701) after uptake of two Gram-positive (Listeria monocytogenes and Staphylococcus aureus) and two Gram-negative bacteria (Salmonella typhimurium and Legionella pneumophila) characterized by their varying abilities to enter, survive, and replicate in human macrophages. Comparing the results obtained with Gram-negative and Gram-positive bacteria, Stat-1 activation in macrophages does not seem to be related to LPS content. The p-tyr701Stat-1 expression levels were found to be independent of the internalized bacterial number and IFN-γ release. On the contrary, Jak/Stat-1 pathway activation only occurs when an active infection has been established in the host macrophage, and it is plausible that the differences in the expression levels of p-tyr701Stat-1 could be due to different survival mechanisms or to differences in bacteria life cycles within macrophages.